Embedded System Technology : c - Zhang, Xing.; Wu, Zhonghai; Sha, Xingmian; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 13th National Conference on Embedded System Technology, ESTC 2015, held in Beijing, China, in October 2015. The 18 revised full papers presented were carefully reviewed and selected from 63 papers. The topics cover a broad range of fields focusing on research about embedded system technologies, such as smart hardware, system and network, applications and algorithm.
Smart hardware -- System and network -- Applications and algorithm. .
Keywords: Computer network architectures; Computer Communication Networks; Computer system performance; Software engineering; Microprogramming; Computer System Implementation; Computer Communication Networks; System Performance and Evaluation; Special Purpose and Application-Based Systems; Control Structures and Microprogramming